Portal vein ligation and in situ liver splitting in metastatic liver cancer - Aghayeva, Afag (Turk J Surg, 2018)
The most serious complication after major liver resection is liver failure. Depending on preoperative liver function, a future liver remnant of 25%–40% is considered sufficient to avoid postoperative liver failure. A new technique known as portal vein ligation combined with in situ splitting has been developed to obtain rapid liver hypertrophy. Herein, we present a case where we performed portal vein ligation combined with in situ splitting. A 37-year-old male patient with a diagnosis of sigmoid adenocarcinoma and liver metastasis underwent anterior resection because of an obstructing sigmoid tumor and received palliative chemotherapy. After chemotherapy, abdominal computed tomography revealed a lesion, 50 mm in diameter, localized between segments 5–8 of the liver on the bifurcation of the anteroposterior segmental branch of the right portal vein. Computed tomography volumetric assessments of the liver were performed in the preoperative period, and it was found that the remnant left liver volume was less than 25%. In the first stage, portal vein ligation and in situ splitting of the liver parenchyma were performed. On the second and sixth postoperative days, computed tomography revealed hypertrophy of the left liver lobe. On the sixth day, a right hepatectomy was performed. Portal vein ligation combined with in situ splitting has been used by surgeons worldwide to obtain rapid and adequate liver hypertrophy. This new approach yields hope for patients with locally advanced liver tumors and may increase the number of curative resections for primary or metastatic liver tumors.